2020
DOI: 10.31744/einstein_journal/2020ai5822
|View full text |Cite
|
Sign up to set email alerts
|

Lung cavitation in COVID-19: co-infection complication or rare evolution?

Abstract: Figure 2. Bedside anteroposterior chest X-ray images demonstrate the radiographic evolution of the nosocomial infection with multiple areas of consolidation in both lungs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…None had received prior immunosuppression. All 12 were males, required invasive mechanical ventilation, and the median (range) time from symptom onset to invasive mechanical ventilation was 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) days. Three were admitted directly via our institution's Emergency Department and intubated within 24 hours, and nine patients were transferred from other hospitals within 72 hours of intubation.…”
Section: Resultsmentioning
confidence: 99%
“…None had received prior immunosuppression. All 12 were males, required invasive mechanical ventilation, and the median (range) time from symptom onset to invasive mechanical ventilation was 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) days. Three were admitted directly via our institution's Emergency Department and intubated within 24 hours, and nine patients were transferred from other hospitals within 72 hours of intubation.…”
Section: Resultsmentioning
confidence: 99%
“…Zantah et al [ 186 ] reported six cases of SPX in 902 patients with COVID-19 pneumonia with an incidence of 0.66%. Lung cavitations have also been reported as rare complications in COVID-19 pneumonia and can be due to cavitation of pulmonary infarctions or caused by destructive pulmonary fibrosis in the late phase of the disease, or associated with necrotizing pneumonia [ 194 , 195 ].…”
Section: Covid-19 Complicationsmentioning
confidence: 99%
“…A small number published single patient case reports have more recently reported pulmonary cavitation [10][11][12] , but this is considered a rare event. In contrast, experience at our tertiary care referral hospital differed.…”
Section: Introductionmentioning
confidence: 99%